2019
DOI: 10.1111/evj.13114
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of strangles associated with a novel genotype of Streptococcus equi subspecies equi in donkeys in China during 2018

Abstract: Summary Background Strangles is a highly contagious respiratory disease of equids caused by the bacterium Streptococcus equi subspecies equi. Objectives To identify the cause of an outbreak of strangles that occurred on donkey farms within the Shandong Province of China and determine the prevalence of the disease. Study design Cross‐sectional. Methods Samples were taken from clinically affected animals to measure the prevalence of strangles within the population of donkeys at six intensive farms in China and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Comparing with equivalent N-terminal variable regions from all SeM alleles available in databases (Kelly et al, 2006), identified that the 5' SeM sequence of the CN190402 strain (GenBank accession number MK988511) contained a novel SeM allele, i.e., SeM-138 (https://pubmlst.org/szooepidemicus/seM/). Phylogenetic analysis showed that CN190402 was clustered into a group with SeM-88 and SeM-136, closely related to the SeM-136 that was associated with a strangles outbreak in an intensive donkey farm located in middle-east of China during 2019 (Dong et al, 2019). Comparison of the nucleotide sequences among SeM-3 (4047 strain; GenBank FM204883), SeM-88, SeM-136, and SeM-138 identified that SeM-138 shares 94.2, 96.6 and 98.5% identities, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing with equivalent N-terminal variable regions from all SeM alleles available in databases (Kelly et al, 2006), identified that the 5' SeM sequence of the CN190402 strain (GenBank accession number MK988511) contained a novel SeM allele, i.e., SeM-138 (https://pubmlst.org/szooepidemicus/seM/). Phylogenetic analysis showed that CN190402 was clustered into a group with SeM-88 and SeM-136, closely related to the SeM-136 that was associated with a strangles outbreak in an intensive donkey farm located in middle-east of China during 2019 (Dong et al, 2019). Comparison of the nucleotide sequences among SeM-3 (4047 strain; GenBank FM204883), SeM-88, SeM-136, and SeM-138 identified that SeM-138 shares 94.2, 96.6 and 98.5% identities, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Although strangles is widely reported in horses, only a few strangles cases have been reported in donkeys with severe clinical signs. In our previous study, the strangles outbreak in donkey was first reported in intensive donkey farming (Dong et al, 2019). The investigation presumed that the causative S. equi entered the farm with newly introduced donkeys, which suggested it is important to use quarantine measures effectively and screening methods should be used to identify the infected animals and carriers of S. equi to prevent the spread of strangles.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, compared to Animals 2020, 10, 718 4 of 22 horses and other domesticated animals, knowledge about the reproductive physiology of donkeys and donkey breeding management is still very limited [34][35][36][37][38][39][40]. In addition, intensive donkey farming is a relatively recent development, mainly for the production of donkey dairy products in Europe and for donkey hides but also meat and dairy in China [23,34,[41][42][43][44][45]. To date, intensive donkey farming is still under-researched and knowledge on donkey farming systems is very limited.…”
Section: Approachmentioning
confidence: 99%
“…The farming system starts with an initial female breeding stock. Intensive farming of donkeys is already happening in China [23,44,47]. The latest donkey population estimate is 2.5 million donkeys in China in 2018 [15].…”
Section: The Donkey Farming System Modelmentioning
confidence: 99%
See 1 more Smart Citation